879 Attitudes to Research and Academic Careers Among Surgical Trainees and Medical Students: A Survey of Attendees at the 2021 Oxford Surgical Innovation Conference. (19th August 2022) - Hennessy, C; Brameier, D; Williams, M; McVeigh, J; Handa, A
Abstract: Introduction: Participation in research throughout medical training is essential in developing and implementing evidence-based practice. Increasing competitiveness across many surgical specialties has led to increased desire to participate in research by medical students and surgical trainees of all grades, with the aim of increasing their employability. Method: The Oxford surgical innovation conference (OxSI) took place on the 23 rd of April. The 121 attendees were surveyed regarding their attitudes to medical research, levels of research experience, and their confidence in seeking out and engaging with research opportunities. Survey respondents included clinical medical students, foundation trainees, core surgical trainees and higher specialist trainees. Results: From 121 surveyed attendees at OxSI 2021, we received 88 responses (72%). 90% of respondents were interested in/pursuing a surgical career, with 70% interested in a career in academic surgery specifically. Furthermore, 97.8% agreed that engaging in research and innovation are an important part of surgical training. However only 48.9% were actively engaged in research. Furthermore only 26.2% of respondents were confident in engaging in independent research, with 56.8% stating they would not know how to engage in research or pursue new surgical innovations without outside assistance. Conclusions: There is significant interest among medical trainees in research and academic surgical careers. However, many struggle to engage with research due to time constraints, or inadequate exposure to research opportunities. This survey suggests a larger study examining barriers to research exposure and participation could assist in addressing the discrepancy between desire to engage with research and opportunities to do so.